Development of Scratch Learning Multimedia to Improve Mathematical Literacy Skills on Statistics Material - Wati, Arinda Hikma; Pamungkas, Megita Dwi; Krisma, Dita Aldila; Bacatan, Jovenil (FKIP Universitas Lampung, 2025)
Abstract: This study aims to analyse the validity, practicality, and effectiveness of Scratch learning multimedia in improving students' mathematical literacy skills. This research method is Research and Development (R&D) with ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The sample of this research was VIII C students of SMP Negeri 1 Tegalrejo as many as 32 students. The sampling technique used purposive sampling. The data collection techniques were interviews, questionnaires, observation sheets, and tests. The results showed that Scratch learning multimedia was in the very valid category with the acquisition of 80% material validity and 83.56% media validity. Scratch learning multimedia is classified as a very practical category with a percentage of 81.87% based on student responses and 98.33% teacher responses. In addition, this multimedia is effective for improving mathematical literacy skills as evidenced by the difference in pre-test and post-test scores, with an N-Gain value of 0.43 including the moderate category. It can be concluded that the development of Scratch learning multimedia is valid, practical, and effective to improve students' mathematical literacy skills. Keywords: mathematical literacy, scratch multimedia, statistics.